1974
DOI: 10.1145/360827.360831
|View full text |Cite
|
Sign up to set email alerts
|

Attribute based file organization in a paged memory environment

Abstract: The high cost of page accessing implies a need for for more careful data organization in a paged memory than is typical of most inverted file and similar approaches to multi-key retrieval. This article analyses that cost and proposes a method called multiple key hashing which attempts to minimize it. Since this approach is not always preferable to inversion, a combined method is described. The exact specifications of this combination for a file with given data and traffic characteristics is formulated as a mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

1976
1976
2008
2008

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(25 citation statements)
references
References 5 publications
0
25
0
Order By: Relevance
“…In [15] a non-replacement model is assumed and a formula is derived giving the expected number of block hits when blocks are randomly selected. In [9] a combination of multi-key hashing and inverted indices is proposed to achieve better clustering and less block transfers. In [t6] it is assumed that the records do not have equal probabilities to be accessed and formulae are derived giving the expected number of blocks transferred when searching a sequential or random file.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [15] a non-replacement model is assumed and a formula is derived giving the expected number of block hits when blocks are randomly selected. In [9] a combination of multi-key hashing and inverted indices is proposed to achieve better clustering and less block transfers. In [t6] it is assumed that the records do not have equal probabilities to be accessed and formulae are derived giving the expected number of blocks transferred when searching a sequential or random file.…”
Section: Discussionmentioning
confidence: 99%
“…In the next section it will be shown that formula (6) is a very close approximation of formula (8). Now we will provide a new approximate formula to be used in place of formula (9).…”
Section: P(nr Ql) ~ P(ns Q2) R = O S = O T = O ( N -1 -S -T ) P (mentioning
confidence: 98%
“…The second way is to partition the underlying space into cells (i.e., blocks) at fixed positions so that all resulting cells are of uniform size, which is the case when using the uniform grid (e.g., 13,45,59 ), also the standard indexing method for maps. Figure 2(a) is an example of a 4 × 4 uniform grid in which a collection of straight line segments has been embedded.…”
Section: Methods Based On Spatial Occupancymentioning
confidence: 99%
“…Val is a synthesized attribute, since its value moves up the parse tree from the leaves to the root. In Figure 18, we present a parse tree for the unsigned integer 27. Each of the nodes of the parse tree has been augmented with the attribute grammar symbols Val and Condition.…”
Section: Operating Systems Versus Database Systems -An Analogymentioning
confidence: 99%